2000
DOI: 10.1080/14017430050142413
|View full text |Cite
|
Sign up to set email alerts
|

Randomised Training after Myocardial Infarction: Short and Long-term Effects of Exercise Training after Myocardial Infarction in Patients on Beta-blocker Treatment. A Randomized, Controlled Study

Abstract: In this study we assessed the short- and long-term effects of 4-weeks of exercise training (MI) soon after myocardial infarction in patients on beta-blocker treatment. Thirty-seven male patients < or = 65 years of age were included in the study, 19 of them randomized to exercise training (ET) and 18 to a control group (Ctr). Cumulated work (CW), calculated in kiloJoules (kJ), was recorded before immediately after the intervention period and again six months after the MI. In the short term the mean (SD) CW incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Duration of follow-up not reported Giannuzzi 2008 All patients (treatment and control) participated in 3-6 week cardiac rehabilitation programme (including supervised exercise sessions) prior to randomization. Control group was not “usual care” Gielen 2003 No useful outcome data reported. Heldal 2000 No useful outcome data reported. Higgins 2001 No useful outcome data reported. Jiang 2007 No useful outcome data reported. Kentala 1972 Quote: “On admission the patients were divided up according to their year of birth into a control group and a training group…”Not a randomised study. Krachler 1997 No useful outcome data reported. Li 2004 Follow-up <6 months. Liao 2003 Follow-up too short (3-4 weeks) and no useful outcome data reported Mezey 2008 Not a randomised study. Peschel 2007 No useful outcome data reported. Piestrzeniewicz 2004 No useful outcome data reported. Roviaro 1984 Not a randomised study. Assigned to treatment group according to geographic location Schumacher 2006 No useful outcome data reported. Stenlund 2005 No useful outcome data reported. Takeyama 2000 No useful outcome data reported. Tokmakidis 2003 No useful outcome...…”
Section: Characteristics Of Included Studies [Ordered By Study Id]mentioning
confidence: 99%
“…Duration of follow-up not reported Giannuzzi 2008 All patients (treatment and control) participated in 3-6 week cardiac rehabilitation programme (including supervised exercise sessions) prior to randomization. Control group was not “usual care” Gielen 2003 No useful outcome data reported. Heldal 2000 No useful outcome data reported. Higgins 2001 No useful outcome data reported. Jiang 2007 No useful outcome data reported. Kentala 1972 Quote: “On admission the patients were divided up according to their year of birth into a control group and a training group…”Not a randomised study. Krachler 1997 No useful outcome data reported. Li 2004 Follow-up <6 months. Liao 2003 Follow-up too short (3-4 weeks) and no useful outcome data reported Mezey 2008 Not a randomised study. Peschel 2007 No useful outcome data reported. Piestrzeniewicz 2004 No useful outcome data reported. Roviaro 1984 Not a randomised study. Assigned to treatment group according to geographic location Schumacher 2006 No useful outcome data reported. Stenlund 2005 No useful outcome data reported. Takeyama 2000 No useful outcome data reported. Tokmakidis 2003 No useful outcome...…”
Section: Characteristics Of Included Studies [Ordered By Study Id]mentioning
confidence: 99%
“…CR should be recommended especially for patients with exercise intolerance after MI [ 23 , 24 , 25 ]. The increase in physical performance during CR in our patients was 14.4%, while the increase in value for non-rehabilitated patients is usually lower than 5% and not statistically significant [ 26 , 27 ]. The reported increase in physical performance during CR in patients after MI ranges between 14% and 32% [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies9, 18, 19 ) have also shown that exercises, if udertaken at moderate intensities, can result in improvements in health and aerobic capacity. After acute MI, aerobic exercise promotes a decrease in percentage body fat23 ) , HRmax19 ) , reduces blood pressure22 ) , and increases VO2peak23 ) .…”
Section: Introductionmentioning
confidence: 89%
“…Cardiorespiratory capacity has been shown to improve during training in post-myocardial infarction patients9 ) . Exercises that are prescribed for individuals with MI have changed over the years, ranging from standard exercises meant for everyone, all the way to exercises tailored to each individual, which are created on the basis of risk factors, age and state of function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation